Platinum-Based Adjuvant Chemotherapy for Stage II and Stage III Squamous Cell Carcinoma of the Lung - Isaka, Tetsuya (Ann Thorac Cardiovasc Surg, 2016)
Introduction: The efficacy of platinum-based adjuvant chemotherapy (PBAC) for pathological stage II and stage III squamous cell carcinoma (SCC) of the lung was analyzed retrospectively. Materials and Methods: The prognoses of 94 patients with stage II and stage III SCC with or without PBAC (more than three courses of cisplatin-, carboplatin-, and nedaplatin-based adjuvant chemotherapy) were compared. Results: The mean observation period was 46.1 months. PBAC was not administered for the following reasons: 39 (55.7%) patients had comorbidities, 25 (35.7%) were older than 75 years, 19 (27.1%) patients underwent surgery before the approval of PBAC, and 3 (4.3%) patients could not continue PBAC (≤2 cycles) because of adverse events. PBAC patients (n = 24) were significantly younger than non-PBAC patients (n = 70; 66.3 vs 69.6 years old, respectively; p = 0.043). Disease-free survival (DFS) did not differ between PBAC and non-PBAC patients (55.0% and 67.1%, respectively; p = 0.266). PBAC patients tended to have worse overall survival (OS) than non-PBAC patients (56.1% and 70.2%, respectively; p = 0.138). PBAC was not prognostic for OS (hazard ratio (HR), 2.11; 95% confidence interval (CI), 0.82%–5.40%; p = 0.120). Conclusion: PBAC did not improve the prognoses of patients with pathological stage II or stage III SCC in the single institution experience.